2020
DOI: 10.4314/sajas.v50i1.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zinc nanoparticles on embryo and chicken growth, and the content of zinc in tissues and faeces

Abstract: The hypothesis was that owing to their high bioavailability, zinc oxide nanoparticles (NanoZnO) can effectively replace (Zn) salts and reduce Zn excretion with faeces. The objective of this study was to investigate the effects of NanoZnO on the development of chicken embryos, the growth of broiler chickens, and Zn excretion with faeces. At day 1 of incubation, 120 eggs were randomly divided between a control group (not injected) and groups injected with a hydrocolloid of NanoZnO in increasing concentrations (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…After cooling, selected organs were collected (liver, muscle, and both femurs and tibias), weighed, and stored at −80 °C. IOI procedure and the minimum necessary sample size estimation were performed with minor modifications as described by Lukasiewicz et al and Pineda et al [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…After cooling, selected organs were collected (liver, muscle, and both femurs and tibias), weighed, and stored at −80 °C. IOI procedure and the minimum necessary sample size estimation were performed with minor modifications as described by Lukasiewicz et al and Pineda et al [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Te same results showed that nano-Znimproved the broiler weight and immune system organs [5,25]. Tis result does not agree with Hasan [26] and Łukasiewicz et al [1] who showed that replacing ZnO withZnO nanoparticles had no benefcial efect on broiler performance.Numerous studies on broilers have shown thatnano-Zn has higher bioavailability compared to the traditionalZn source, suggesting that measuring the concentrationof minerals in organs could allow a more accurateassessment of nanoparticle bioavailability [23,24,27].…”
Section: Histology Samples and Measurementsmentioning
confidence: 96%
“…Zinc plays an important role in many biological activities that occur in the body [1] and is considered an important nutrient for poultry, and Zn is commonly added as a supplement to all formulated poultry diets at a rate of 0.012-0.018% [2]. Te biological activity of Zn is required for growth and skeletal development [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation